A risk signature based on necroptotic-process-related genes predicts prognosis and immune therapy response in kidney cell carcinoma - Li, Jingxian; Liu, Xun; Qi, Yuanjiong; Liu, Yang; Du, E.; Zhang, Zhihong (Frontiers in Immunology, 2022)
Necroptosis is a regulated form of cell necroptotic process, playing a pivotal role in tumours. In renal cell cancer (RCC), inhibiting necroptosis could promote the proliferation of tumour cells. However, the molecular mechanisms and prognosis prediction of necroptotic process-related genes in RCC still unclear. In this study, we first identified the necroptotic process prognosis-related genes (NPRGs) by analyzing the KIRC of The Cancer Genome Atlas (TCGA, n=607). We systematically analyzed the expression alteration, clinical relevance, and molecular mechanisms of NPRGs in renal clear cell carcinoma. We constructed an NPRGs-risk signature using the least absolute shrinkage and selection operator (LASSO) regression analysis based on the expression of 7 NPRGs. We found that the overall survival (OS) of KIRC patients was significantly different in high/low-NPRGs-risk groups. Univariate/multivariate Cox regression showed that the NPRG-risk signature was an independent prognosis factor in RCC. The Gene Set Variation Analysis (GSVA) and gene set enrichment analysis (GSEA) was used to explore the molecular mechanisms of NPRGs. Immune-/metabolism-related pathways showed differential enrichment in high/low-NPRGs-risk groups. The E-MTAB-1980, TCGA-KIRP, GSE78220, Alexandra et al.’s cohort, and IMvigor210 cohort datasets were respectively used as independent validation cohorts of NPRGs-risk signature. The patients in high-/low-NPRGs-risk groups showed different drugs sensitivity and immune checkpoint expression, and immune therapy response. Finally, we established a nomogram based on the NPRGs-risk signature, stage, grade, and age for eventual clinical translation; the nomogram possesses an accurate and stable prediction effect. The signature could predict the prognosis and therapy response of patients, which provide the foundation for further clinical therapy strategies for RCC patients.